Vann McGee, Truth, Vagueness, and Paradox. An Essay on the Logic of Truth. Giovanni Sommaruga-Rosolemos, Fixed Point Constructions in Various Theories of Mathematical Logic - Jesús Padilla Gálvez (Crítica)
Resumen